Teaching Teaching Extensive Reading to EFL and Non-EFL Students: Benefits and Problems: Keywords: extensive reading, reading, reading English, teaching reading - Nur Fitria, Tira (English Education Program, Education Faculty, Universitas Nurul Huda, 2023)
This research describes the benefits and problems during the teaching of Extensive Reading (ER). This research is library research. The analysis shows that extensive reading has several benefits in the teaching and learning process, especially in learning English as a foreign language, such as adding vocabulary, helping to understand grammar, building reading speed, and reading fluency, reading for getting pleasure, building confidence and motivation, increasing motivating to read English more. Several difficulties of ER are also identified throughout the long reading exercise in extensive reading, including poor/lack of vocabulary and grammatical skills, inconsistent reading, difficulty comprehending the meaning of words, and loud classroom environment influence concentration on text analysis. Other problems are the level of reading material or difficulty in analyzing material related to literary works, different academic grades, learners paying less attention to the program, and the ER material selection. In selecting materials for extensive reading (ER), appropriate reading materials constitute an essential foundation of ER program. Students need a large quantity of engaging, approachable, readily available materials if they are to read extensively. Teachers should choose student-centered activities so students have opportunities to appreciate themselves with interactive reading experiences. The extensive reading (ER) program in schools/institutions also can be developed students' passion for reading in English. It is not only a skill or a translation, but also a personal, social, and academic activity. To be successful in ER program implementation, several aspects must be considered which involve all parties including schools/institutions, students, teachers, and even parents.